Intramedullary Mg2Ag nails augment callus formation during fracture healing in mice. (May 2016) - Jähn, Katharina; Saito, Hiroaki; Taipaleenmäki, Hanna; Gasser, Andreas; Hort, Norbert; Feyerabend, Frank; Schlüter, Hartmut; Rueger, Johannes M.; Lehmann, Wolfgang; Willumeit-Römer, Regine; Hesse, Eric
Graphical abstract: Abstract: Intramedullary stabilization is frequently used to treat long bone fractures. Implants usually remain unless complications arise. Since implant removal can become technically very challenging with the potential to cause further tissue damage, biodegradable materials are emerging as alternative options. Magnesium (Mg)-based biodegradable implants have a controllable degradation rate and good tissue compatibility, which makes them attractive for musculoskeletal research. Here we report for the first time the implantation of intramedullary nails made of an Mg alloy containing 2% silver (Mg2Ag) into intact and fractured femora of mice. Prior in vitro analyses revealed an inhibitory effect of Mg2Ag degradation products on osteoclast differentiation and function with no impair of osteoblast function. In vivo, Mg2Ag implants degraded under non-fracture and fracture conditions within 210 days and 133 days, respectively. During fracture repair, osteoblast function and subsequent bone formation were enhanced, while osteoclast activity and bone resorption were decreased, leading to an augmented callus formation. We observed a widening of the femoral shaft under steady state and regenerating conditions, which was at least in part due to an uncoupled bone remodeling. However, Mg2Ag implants did not cause any systemic adverse effects. These data suggest that Mg2Ag implants might be promising for intramedullary fixation of long bone fractures, a novel concept that has to be further investigated in future studies. Statement of Significance: Biodegradable implants are promising alternatives to standard steel or titanium implants to avoid implant removal after fracture healing. We therefore developed an intramedullary nail using a novel biodegradable magnesium-silver-alloy (Mg2Ag) and investigated the in vitro and in vivo effects of the implants on bone remodeling under steady state and fracture healing conditions in mice. Our results demonstrate that intramedullary Mg2Ag nails degrade in vivo over time without causing adverse effects. Importantly, radiographs, μCT and bone histomorphometry revealed a significant increase in callus size due to an augmented bone formation rate and a reduced bone resorption in fractures supported by Mg2Ag nails, thereby improving bone healing. Thus, intramedullary Mg2Ag nails are promising biomaterials for fracture healing to circumvent implant removal.